THE TRANSITION OF SINULOG DANCE FESTIVAL IN THE FACE OF MODERNIZATION - Ortiz, Ersa Joy L.; Relampagos, Faith Joan; Pejana, Jyn Ruehn; Siarot, Shene Mitchelle; Tolo, Nino Aaron; Melchor, Ruby S.; Inocian, Reynaldo B. (International Journal of Research -GRANTHAALAYAH, 2017)
This study analyzed the evolutionary transition of the Sinulog-based dance in Cebu, Philippines. It also sought to: contrast the traditional Sinug Dance and the contemporary Sinulog-based dance in terms of the dance steps, musicality, ritual, costumes, and the reason or purpose of dancing; identify the effects of the changes in the Sinulog-based dance in the tourism industry of Cebu City as a whole; generate a theory which serves as framework of the evolutionary transition of the Sinulog-based dance. A collective case study design with naturalistic observation was utilized. The transition of the traditional Sinug dance to the contemporary Sinulog dance was ignited by the change of external factors indicated in the Theory of Cultural Transition. The traditional Sinug dance was on the brink of extinction without the help of certain individuals and organization who took part in preserving this potential cultural heritage, as a response to the essentialist challenge posed by the cultural heritage advocates. The contemporary Sinulog dance transcended to a new culture after the Sinug was obliterated to a more progressivist view of change to increase tourist attraction catapulted to a more commercialized endeavor for tourism and business development opportunities.